2022
DOI: 10.3390/air1010002
|View full text |Cite
|
Sign up to set email alerts
|

Non-Road Mobile Machinery Emissions and Regulations: A Review

Abstract: Non-Road Mobile Machinery (NRMM) incorporate a wide range of machinery, with or without bodywork and wheels, and are installed with a combustion engine and not intended for carrying passengers or goods on the road. These are used in many different sectors including construction, agriculture, forestry, mining, local authorities, airport and port ground operations, railways, inland waterways and within the household and gardening sector. This article presents a review of the state of knowledge with regard to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Hagan et al's classification categorizes non-road mobile machines based on their usage characteristics, as detailed in Table 2 [3,25]. For instance, various vehicles exhibit distinct purposes and configurations within the agricultural sector alone, illustrated in Figure 1.…”
Section: Classification By Usagementioning
confidence: 99%
See 1 more Smart Citation
“…Hagan et al's classification categorizes non-road mobile machines based on their usage characteristics, as detailed in Table 2 [3,25]. For instance, various vehicles exhibit distinct purposes and configurations within the agricultural sector alone, illustrated in Figure 1.…”
Section: Classification By Usagementioning
confidence: 99%
“…A study conducted in Poland compared the fuel consumption of farming machinery between 2012 and 2013. The findings indicated that emissions from agricultural non-road machines had a higher impact on the total emissions of CO (39.837 tonnes), NOx (42.281 tonnes), hydrocarbons (8072 tonnes), and PM (3947 tonnes) [3]. An alternative for reducing these emissions is through the electrification of the powertrain of these machines.…”
Section: Introductionmentioning
confidence: 99%
“…Emissions are calculated for a given class of postvehicle traffic conditions for assumed traffic conditions. Emission calculations take into account model calibration factors such as operating condition, vehicle specifications, and the surrounding environment [76,77].…”
Section: Macroscopic Emission Modelsmentioning
confidence: 99%
“…Different countries have varying standards for limiting CO emissions from automobiles [41]. In order to mitigate the impact of vehicle emissions on the environment and improve air quality, China has implemented the sixth phase of measurement methods for automobile pollutants and emission limits [42,43].…”
Section: Boundary Conditions 231 Ventilation Conditionsmentioning
confidence: 99%